Food Intakes Mediate Ethnic Differences in the Gut Microbiome. (7th June 2021) - Borrello, Kirra; Park, Song-Yi; Lim, Unhee; Maskarinec, Gertraud; Boushey, Carol; Wilkens, Lynne; Randolph, Timothy; Marchand, Loïc Le; Hullar, Meredith; Lampe, Johanna
Abstract: Objectives: Gut microbial composition has been associated with diet quality and health outcomes and has also been found to vary across ethnic groups. We explored how ethnic differences in food consumption may mediate some of the ethnic variation in the gut microbiome (GM). Methods: In a subset of 5, 280 Multiethnic Cohort participants, based on a food frequency questionnaire administered in 2003–2008, we assessed overall diet quality using the Healthy Eating Index (HEI-2015; scores 0–100) and specific food consumption using the intake amounts of 10 component food groups used to define common diet quality indexes. GM composition was obtained from 16S rRNA gene sequencing of a stool sample (2013–2016; age 59–98 years) and estimated in genus proportions (as the centered log ratio (CLR) transformed counts). Using mediation analysis, we determined the % of the total ethnicity effect on the genus proportion for each of the ethnically divergent bacterial genera mediated by overall diet quality and component food groups, while adjusting for age, sex, total energy intake, body mass index, and antibiotics use. Results: Overall diet quality was highest in Whites (mean HEI-2015 = 73.1) and African Americans (72.7), followed by Japanese Americans (71.3), Native Hawaiians (70.1) and Latinos (68.9). Of the 152 genera, 7 with the largest ethnic variation (CLR difference for the genus between most vs. least abundant ethnic group > 1) were examined for mediation. Five genera showed significant mediation of their ethnic differences through diet ( P < 0.00, 045 for Bonferroni correction), ranging from the −12% for Flavonifractor in African Americans vs. Whites mediated by vegetable intake to the 19% for Christensenellaceae R-7 group in Latinos vs. Whites mediated by overall diet quality. Large mediation effects were also seen by saturated fat for Ruminococcaceae NK4A214 in African Americans vs. Whites (18%) and by alcohol for Erysipelatoclostridium in Latinos vs. Whites (18%). Conclusions: Overall diet quality and component foods may contribute substantially to ethnic differences in gut bacterial composition. These novel findings may help the development of targeted dietary interventions to improve the gut health of specific ethnic groups. Funding Sources: This work was supported by the US National Cancer Institute (NCI) grants P01 CA168530, U01 CA164973, and P30 CA71789.